Organization readiness of server virtualization at Jabatan Pendaftaran Negara (JPN) / Rozidah Abdullah - Abdullah, Rozidah (2016)
The historical general trend in organizations is that each time a new application is added the information technology (IT) department is tasked with adding a new server. It is common to find several servers in one organization allocated to different tasks like mails, central repository for office files, customer database and many others. This is not only expensive but also consumes office space hence calling for increased physical security to protect the many increasing number of servers. Malaysia government agency has significantly shown interest in adopting virtualization technology. MAMPU had outlined strategic directions for the implementation of Public Sector ICT that focuses on efficiency, productivity and innovation for the purpose of optimizing service delivery to the citizens. MAMPU encourage agencies under its approach and the use of green technology in the implementation of ICT Open Source Software, Digital Innovation, Green Technology, Anchored People and Anchored Data. On the Basic Principles of Green Technology, MAMPU encourage agencies to use of green technology in the implementation of ICT. Henceforth, this study aims to identify the factors that contribute to organizational readiness for server virtualization in Jabatan Pendaftaran Negara (JPN). The Technological, Organizational and Environmental (TOE) framework is used in this study looks into three component- Technology Readiness, Organisation Readiness, and Environment Readiness. A questionaire was conducted with eighty two respondents in JPN. SPSS was used for data analysis. Results showed that hardware and software, infrastructure, people and vendor have relationship with server virtualization in organization readiness for JPN. Cost have no relationship with server virtualization.